Equilibrium sorption isotherm studies of Cd(II), Pb(II) and Zn(II) ions detoxification from waste water using unmodified and EDTA-modified maize husk - Igwe,Jude C (Pontificia Universidad Católica de Valparaíso, 2007)
The mobilization of heavy metals in the environment due to industrial activities is of serious concern due to the toxicity of these metals in humans and other forms of life. The equilibrium adsorption isotherms of Cd(II), Pb(II) and Zn(II) ions, detoxification from waste water using unmodified and EDTA-modified maize husk have been studied. Maize husk was found to be an excellent adsorbent for the removal of these metal ions. The amount of these metal ions adsorbed increased as the initial concentration increased. Also, EDTA-modification enhanced the adsorption capacity of maize husk due to the chelating ability of ethylenediamine tetra acetic acid (EDTA). Among the three adsorption isotherms tested, Dubinin-Radushkevich isotherm gave the best fit with R² value ranging from 0.7646 to 0.9988 and an average value of 0.9321. This is followed by Freundlich and then Langmiur isotherms. The sorption process was found to be mostly a physiosorption process as seen from the apparent energy of adsorption which ranged from 1.03 KJ/mol to 12.91 KJ/mol. Therefore, this study demonstrates that maize husk which is an environmental pollutant could be used to adsorb heavy metals and achieve environmental cleanliness.